Karakteristik Pasien Demam Berdarah Dengue Rawat Inap di Rumah Sakit Umum UKI Tahun 2020 - Diah putri Ayu Islammia; Nanda Aula Rumana; Laela Indawati; Deasy Rosmala Dewi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus (DEN) which is spread through mosquito bites. This research is a quantitative descriptive study using a non-random sampling method with a saturated sample technique. The study was conducted at the UKI General Hospital with a sample of 94 patients. The results showed that the age of the most patients was 17-25 years, 30 patients (32%), the most gender were male (60%), domiciled in East Jakarta (70%), the most occupations were self-employed (36%), months The highest incidence was in March 23 patients, the most felt symptom was fever (100%), the highest severity level based on the ICD-10 code was A97.0 94 patients (100%), the category of platelet count when it arrived was abnormal (93 %), while the category of the number of platelets at home is normal (10%), the category of the number of hematocrit is abnormal (43%), while the category of the number of hematocrit when going home is normal (51%), the ICD-10 code used is A91 , the longest length of hospitalization was <6 days 67 patients (71%). The condition when he returned home was healed (99%).